Acute toxicity of cyanide (KCN) on two types of marine larvae: Acropora sp. planulae and D-veliger larvae of Tridacna squamosa. (April 2019) - Werorilangi, S; Yusuf, S; Massinai, A; Rastina,; Niartiningsih, A; Tahir, A; Nimzet, R; Afdal, M; Karimah, A Z; Umar, W
Abstract: Cyanide fishing has been intensively used to catch aquarium fishes and fish for human consumption around coral reefs in the South East Asian countries, such as Indonesia. There is little known about the lethal effect of cyanide on the early life stages of marine organisms. We assessed mortality and morphological changes of Acropora sp. planulae and fluted giant clam ( Tridacna squamosa ) D-veliger larvae exposed to potassium cyanide (KCN) concentrations closed to those used in cyanide fishing. The KCN concentration exposure treatments for coral planulae were 50, 100, 300, 600, and 1000 mg L −1 ; and those for giant clam D-veliger larvae were 18.875, 37.5, 75, 300, and 600 mg L −1 . The 24 hour static-acute toxicity test was used with four replicates for each concentration. The 24h-LC50 was calculated based on Finney's Probit Analysis Method, and the 24 h-LC50 for coral planulae and giant clam veliger were 121.854 and 84.421 mg L −1, respectively. The D-veliger larvae of Tridacna squamosa were more sensitive to KCN exposure than Acropora sp . planulae. In addition to mortality, we observed that, in both the planulae and D-veliger larvae, morphological abnormalities increased in frequency and severity with increasing KCN concentration, even at the lowest KCN concentrations.